Light-Driven Biosynthesis of myo-Inositol Directly From CO2 in Synechocystis sp. PCC 6803 - Wang, Xiaoshuai; Chen, Lei; Liu, Jing; Sun, Tao; Zhang, Weiwen (Frontiers in Microbiology, 2020)
myo-inositol (MI) is an essential growth factor, nutritional source, and important precursor for many derivatives like D-chiro-inositol. In this study, attempts were made to achieve the “green biosynthesis” of MI in a model photosynthetic cyanobacterium Synechocystis sp. PCC 6803. First, several genes encoding myo-inositol-1-phosphate synthases and myo-inositol-1-monophosphatase, catalyzing the first or the second step of MI synthesis, were introduced, respectively, into Synechocystis. The results showed that the engineered strain carrying myo-inositol-1-phosphate synthase gene from Saccharomyces cerevisiae was able to produce MI at 0.97 mg L–1. Second, the combined overexpression of genes related to the two catalyzing processes increased the production up to 1.42 mg L–1. Third, to re-direct more cellular carbon flux into MI synthesis, an inducible small RNA regulatory tool, based on MicC-Hfq, was utilized to control the competing pathways of MI biosynthesis, resulting in MI production of ∼7.93 mg L–1. Finally, by optimizing the cultivation condition via supplying bicarbonate to enhance carbon fixation, a final MI production up to 12.72 mg L–1 was achieved, representing a ∼12-fold increase compared with the initial MI-producing strain. This study provides a light-driven green synthetic strategy for MI directly from CO2 in cyanobacterial chassis and represents a renewable alternative that may deserve further optimization in the future.